Impactos ambientais: uso de agrotóxicos, análise da qualidade da água em microbacias do Rio Fortaleza/RS - Brasil - Deitos, Tandara (2024)
Water is an essential resource for life, playing a crucial role in human health and environmental sustainability. In Brazil, the intensive use of pesticides in agricultural practices has significant impacts on water resources, requiring a greater understanding of their effects. This study aimed to assess pesticide contamination and water quality in the Fortaleza River Basin, in northwestern Rio Grande do Sul, Brazil. Analyses were performed on 40 water samples collected in four campaigns between December 2023 and March 2024. Using advanced analytical methodologies and remote sensing, relationships between intensive pesticide use, land use changes, and water resource management were identified. The results showed the presence of residues of twelve pesticides, including 2,4-D, Tebuconazole, Diuron, Carbendazim, Atrazine, Clothianidin, Dicamba, Imidacloprid, Imazetapyr, Methoxyfenozide, Simarzine and Chlorantraniliprole. In addition, high levels of total coliforms and Escherichia coli were found, compromising the microbiological quality of the water. Areas with greater vegetation cover have lower levels of contamination, reducing the positive influence of vegetation in protecting water resources. Multivariate analyses correlated the intensity of agricultural activity with pollution levels, highlighting the impact of inadequate soil management and the replacement of native vegetation by monocultures. The research found that 81% of the samples contained pesticide residues, with 23% exceeding the limits established by Brazilian legislation. The data reinforce the need for more sustainable agricultural practices and rigorous public policies to balance economic development and environmental preservation. The suggested measures include integrated regulatory management, use of precision technologies, soil conservation and restoration of degraded areas, in addition to strengthening monitoring and awareness of local communities. The findings provide crucial information to guide mitigation actions and promote environmental sustainability, ensuring the protection of water resources and public health in the micro-basins of the Fortaleza River.